2020
DOI: 10.3390/ijerph17176085
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aviation Safety through Modeling Accident Risk Assessment of Runway

Abstract: The exponential increase in aviation activity and air traffic in recent decades has raised several public health issues. One of the critical public health concerns is runway safety and the increasing demand for airports without accidents. In addition to threatening human lives, runway accidents are often associated with severe environmental and pollution consequences. In this study, a three-step approach is used for runway risk assessment considering probability, location, and consequences of accidents through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Another gap that has been followed in this study is the lack of a comprehensive, practical, scientific method for bridge networks in Iran. Although there are attempts in the field of developing health monitoring methods for various infrastructures in Iran, such as [28][29][30][31][32][33][34][35][36][37]; however, the absence of a full detailed, efficient, specialized method for bridges can be felt. Consequently, the authors also tried to fill the later gap, and therefore, the proposed method is based on the condition of bridges in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Another gap that has been followed in this study is the lack of a comprehensive, practical, scientific method for bridge networks in Iran. Although there are attempts in the field of developing health monitoring methods for various infrastructures in Iran, such as [28][29][30][31][32][33][34][35][36][37]; however, the absence of a full detailed, efficient, specialized method for bridges can be felt. Consequently, the authors also tried to fill the later gap, and therefore, the proposed method is based on the condition of bridges in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature focused on aviation safety modelling and assessing accident risk at airports. In particular, different areas of the airport airside have been analysed to identify the best strategies [ [15] , [16] , [17] , [18] ]. Indeed, the construction and adaptation of the airport infrastructures and facilities should comply with the criteria of the airspace configuration [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that exposure to PETs for a long time may lead to health risk to animals and humans [ 5 ]. For instance, acute and chronic as exposure would cause an imbalance in the cardiovascular system and other organs, which may finally lead to cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%